Nitroarenes as Antitubercular Agents: Stereoelectronic Modulation to Mitigate Mutagenicity. Issue 3 (11th January 2016) - Landge, Sudhir; Ramachandran, Vasanthi; Kumar, Anupriya; Neres, João; Murugan, Kannan; Sadler, Claire; Fellows, Mick D.; Humnabadkar, Vaishali; Vachaspati, Prakash; Raichurkar, Anandkumar; Sharma, Sreevalli; Ravishankar, Sudha; et al.
Abstract: Nitroarenes are less preferred in drug discovery due to their potential to be mutagenic. However, several nitroarenes were shown to be promising antitubercular agents with specific modes of action, namely, nitroimidazoles and benzothiazinones. The nitro group in these compounds is activated through different mechanisms, both enzymatic and non‐enzymatic, in mycobacteria prior to binding to the target of interest. From a whole‐cell screening program, we identified a novel lead nitrobenzothiazole (BT) series that acts by inhibition of decaprenylphosphoryl‐β‐d ‐ribose 2′‐epimerase (DprE1) of Mycobacterium tuberculosis ( Mtb ). The lead was found to be mutagenic to start with. Our efforts to mitigate mutagenicity resulted in the identification of 6‐methyl‐7‐nitro‐5‐(trifluoromethyl)‐1, 3‐benzothiazoles (cBTs), a novel class of antitubercular agents that are non‐mutagenic and exhibit an improved safety profile. The methyl group ortho to the nitro group decreases the electron affinity of the series, and is hence responsible for the non‐mutagenic nature of these compounds. Additionally, the co‐crystal structure of cBT in complex with Mtb DprE1 established the mode of binding. This investigation led to a new non‐mutagenic antitubercular agent and demonstrates that the mutagenic nature of nitroarenes can be solved by modulation of stereoelectronic properties. Abstract : Stereoelectronic effects : Nitrobenzothiazoles were identified as antitubercular agents with an excellent microbiological profile. At the start, the series was Ames positive (example6 ). In this study we demonstrate that modulation of electron affinity rendered the series Ames negative. The methylated nitrobenzothiazoles (cBT) were found to be non‐mutagenic (example6 a ). To the best of our knowledge, this is the first use of stereoelectronic effects to mitigate mutagenicity in lead generation.